Percutaneous edge‐to‐edge repair of the mitral valve in patients with degenerative versus functional mitral regurgitation. Issue 1 (6th January 2014) - Braun, Daniel; Lesevic, Hasema; Orban, Martin; Michalk, Fabian; Barthel, Petra; Hoppe, Katharina; Sonne, Carolin; Pache, Jürgen; Mehilli, Julinda; Kastrati, Adnan; Hausleiter, Jörg; Massberg, Steffen
Abstract : Objectives: To prospectively assess the outcome of percutaneous edge‐to‐edge repair in patients with degenerative versus functional mitral regurgitation (MR). Background: The optimal patient population eligible for percutaneous edge‐to‐edge repair has yet to be defined. Methods: We analyzed 119 patients treated by percutaneous edge‐to‐edge repair for symptomatic MR, 72 patients with degenerative and 47 patients with functional MR. The primary endpoints were defined as procedural success (MR grade reduction ≥1 grade) as well as a composite endpoint defined as freedom from MR 3+ or 4+, mitral valve reintervention and death 12 months after clip implantation. In patients with successful clip placement we further analyzed MR grade, New York Heart Association (NYHA) functional class, distance in the 6 min walking test and left ventricular volumes 12 months after clip implantation. Results: The primary success rate of all intended clipping procedures was 83.3% for degenerative and 89.4% for functional MR ( P  = 0.42). Regarding the composite endpoint we observed an event free survival of 59.7% in patients treated for degenerative MR and 63.8% in patients treated for functional MR ( P  = 0.73). We observed a highly significant reduction in MR grade as well as improvement in NYHA functional status in both groups 12 months after clip implantation. However, there was a more pronounced MR grade reduction in patients treated for degenerative MR compared with patients treated for functional MR. Conclusions: Percutaneous edge‐to‐edge repair of the mitral valve is feasible and comparably effective in patients with degenerative and functional MR. © 2013 Wiley Periodicals, Inc.